2012
DOI: 10.2478/v10176-012-0010-5
|View full text |Cite
|
Sign up to set email alerts
|

Application of genetic algorithms to determine heavy metal ions sorption dynamics on clinoptilolite bed

Abstract: In the last decade a growing interest was observed in low-cost adsorbents for heavy metal ions. Clinoptilolite is a mineral sorbent extracted in Poland that is used to remove heavy metal ions from diluted solutions. The experiments in this study were carried out in a laboratory column for multicomponent water solutions of heavy metal ions, i.e. Cu(II), Zn(II) and Ni(II). A mathematical model to calculate the metals' concentration of water solution at the column outlet and the concentration of adsorbed substanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The authors’ own studies did not find Zeolite Bio.Zeo.S.01 to neutralise the negative impact of nickel on biochemical activity of soil. This can be attributed to the selectivity of clinoptilolite in absorbing heavy metal ions from the environment: Pb > Cd > Cs > Cu(II) > Co(II) > Cr(III) > Zn > Ni(II) > Hg(II) (Tomczak and Kamiński 2012 ). As noted earlier, one of the major features of zeolites is the ability to exchange ions with respect to a given mineral and its chemical properties.…”
Section: Resultsmentioning
confidence: 99%
“…The authors’ own studies did not find Zeolite Bio.Zeo.S.01 to neutralise the negative impact of nickel on biochemical activity of soil. This can be attributed to the selectivity of clinoptilolite in absorbing heavy metal ions from the environment: Pb > Cd > Cs > Cu(II) > Co(II) > Cr(III) > Zn > Ni(II) > Hg(II) (Tomczak and Kamiński 2012 ). As noted earlier, one of the major features of zeolites is the ability to exchange ions with respect to a given mineral and its chemical properties.…”
Section: Resultsmentioning
confidence: 99%
“…Boros-Lajszner et al [105] reported that the addition of zeolites (clinoptilolite) determines the reduction of Ni accumulation in oats (11.69%) only grown in sandy silty loam, thus concluding that the efficiency of this mineral in nickel soil remediation is small. According to previous literature data [106], the authors attributed these results to the selectivity of clinoptilolite in absorbing heavy-metal ions (Pb > Cd > Cs > Cu(II) > Co(II) > Cr(III) > Zn >Ni(II) > Hg(II)). Moreover, the granulometric soil composition has a no negligible role.…”
Section: Natural Zeolites and Soil Pollutionmentioning
confidence: 78%
“…Boros-Lajszner et al [17] found that the zeolite under the study also slightly mitigated the negative effects of nickel on soil biochemical activity. Tomczak and Kamiński [40] reported that this might be caused by selectivity in absorbing heavy metals from the environment. The method of use contributed to the better effect of zeolite, as higher enzyme activity was observed in the soil sown with maize.…”
Section: Discussionmentioning
confidence: 99%